The Influence of Negative Emotional Experiences of Childhood on Criminal Activity in Women with Organic Personality Disorder - Kachaeva, M.A.; Dozortseva, E.G.; Nutskova, E.V.; Kharitonova, N.; Shishkina, O.A.; Vasianina, V.I.; Skibina, N.V.; Nazarova, L.N. (Psihologiâ i pravo, 2022)
In order to study the influence of negative emotional experiences of childhood on criminal activity in women with organic personality disorder we investigated group of women, suspected or accused of crimes in criminal cases, who underwent forensic psychiatric examination (n=102) with comparison to group of women, who had not a criminal history (n=50). It is revealed that for women who have committed criminally punishable acts, negative childhood events with many psychogenic and traumatic events are of significant importance. It was revealed that the greatest importance of adverse childhood events with negative emotional experience - abuse, violence (emotional, physical, sexual) in combination with unfavorable social factors of upbringing had a significant pathoplastic and pathokinetic effect on the clinical and dynamic characteristics of the disease and to a certain extent predetermined the formation of criminal activity of this category of persons. They are more likely to have dependence on surfactants. These women were more likely to commit aggressive offenses (murder, grievous bodily harm), while the victim of these crimes was more often a partner (husband, cohabitant). В данном описательном ретроспективном исследовании с целью изучения влияния негативного эмоционального опыта детства на криминальную активность у женщин с органическим расстройством личности (ОРЛ) проведено исследование группы женщин с ОРЛ, подозреваемых или обвиняемых в преступлениях по уголовным делам, прошедших судебно-психиатрическую экспертизу (n=102), и группы сравнения — женщин с ОРЛ, не имевших криминального анамнеза (n=50). Выявлено что для женщин, совершивших уголовно наказуемые деяния, существенное значение имеют негативные события детства с множеством психогенно-травмирующих событий. Выявлено, что наибольшее значение неблагоприятных событий детства с негативным эмоциональным опытом — жестокое обращение, насилие (эмоциональное физическое, сексуальное) — при сочетании с неблагоприятными социальными факторами воспитания оказывали значимое патопластическое и патокинетическое воздействие на клинико-динамические характеристики заболевания и в определенной степени предопределяли становление криминальной активности у данной категории лиц. У них чаще выявлена зависимость от ПАВ. Эти женщины чаще совершали агрессивные правонарушения (убийства, нанесение тяжких телесных повреждений), при этом жертвой этих преступлений чаще был партнер (муж, сожитель).